2020
DOI: 10.1542/peds.2019-2543
|View full text |Cite
|
Sign up to set email alerts
|

Infectious and Autoimmune Causes of Encephalitis in Children

Abstract: BACKGROUND AND OBJECTIVES: Encephalitis can result in neurologic morbidity and mortality in children. Newly recognized infectious and noninfectious causes of encephalitis have become increasingly important over the past decade. METHODS:We retrospectively reviewed medical records from pediatric patients in Houston diagnosed with encephalitis in both an urban and rural catchment area between 2010 and 2017. We conducted an investigation to understand the etiology, clinical characteristics, and diagnostic testing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
36
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 31 publications
5
36
1
1
Order By: Relevance
“…We describe application of metagenomics in the diagnosis of pediatric CNS infections that included all consenting subjects meeting enrollment criteria rather than only a referred subset. As described in previous studies, an infectious etiology was not identified for most subjects with suspected CNS infection [ 5 ]. A putative organism was isolated from CSF in 25 (35.7%) subjects, and, of these, mNGS of the CSF samples identified a pathogen in 20 (28.6%) subjects ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…We describe application of metagenomics in the diagnosis of pediatric CNS infections that included all consenting subjects meeting enrollment criteria rather than only a referred subset. As described in previous studies, an infectious etiology was not identified for most subjects with suspected CNS infection [ 5 ]. A putative organism was isolated from CSF in 25 (35.7%) subjects, and, of these, mNGS of the CSF samples identified a pathogen in 20 (28.6%) subjects ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, our study could have underestimated the prevalence of AE, as patients were required to have increased CSF pleocytosis and/or elevated protein to be diagnosed with encephalitis, and some AE cases have been observed without these findings [ 42 ]. The International Encephalitis Consortium has published guidelines for the identification of encephalitis that might decrease this bias using a combination approach specifically designed to include autoimmune causes [ 43 ], and some recent studies using these less strict criteria reported an AE proportion as high as 26% among all encephalitis cases [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Autoimmune encephalitis (AE), which is characterized by the presence of antineuronal or antiglial antibodies, has been reported to constitute 4.2% and 7.9% of all encephalitis cases in the United States and the United Kingdom, respectively [ 1 , 2 ]. However, some studies reported a markedly higher percentage [ 2 , 3 ] among pediatric patients [ 4 ]. Autoantibodies in AE are classified into 2 main categories: antibodies against neuronal cell surface and against intracellular antigens [ 5 ].…”
mentioning
confidence: 99%
“…Encephalitis is a potentially lethal neurologic disease wherein inflammation of brain parenchyma leads to neurologic dysfunction (8). Although infectious agents are the main cause of encephalitis, cases of autoimmune encephalitis are increasingly being reported (8,9). Since Dalmau et al (10) described anti-NMDAR encephalitis in 2007, epidemiologic studies have implicated anti-NMDAR encephalitis as a predominant cause of autoimmune encephalitis, second only to demyelinating acute encephalitis (9).…”
Section: Discussionmentioning
confidence: 99%